Development of H5P Course Presentation to Improve Student Mathematics Learning Outcomes - Putri, Intan Nur; Arif Abdul Haqq; Saluky, Saluky (Journal of Mathematics Instruction, Social Research and Opinion, 2024)
Educators are the people who are responsible for all educational processes, so it would be better if learning plans were designed before the implementation took place so that student learning outcomes could be optimized. One of the things that needs to be prepared is learning media. The selected learning media must be able to convey the content of the learning material, either in the form of videos, slides, images, or graphics. Course Presentation is an interactive media in the form of slides that can be filled with videos and interactive quizzes equipped with adaptive feedback. This type of research is in the form of R&D with the ADDIE model, which aims to develop Course Presentation as a learning medium that improves students' mathematics learning outcomes. This research took place in class 9F SMPN 2 Sumber, totaling 32 students. The study results showed that Course Presentation was suitable for learning mathematics through an expert validity test analyzed using the V-Aiken formula. The validity of the material was 0.86 with a valid category, and the media validity result was 0.76 with a valid category. In addition to the feasibility of the media, this study also tested Course Presentation to improve students' mathematics learning outcomes; through the Normalized Gain test, students' mathematics learning outcomes increased by 0.5 with the medium category. From this data, it can be concluded that Course Presentation can be used as a learning medium to improve students' mathematics learning outcomes